Economic analysis of innovation tax incentives in Brazil: essays on the impacts of law 11,196/05 on industrial innovation - Colombo, Daniel Gama e (2017)
The objective of this thesis is to empirically assess how the tax incentives of Law 11,196/05 have affected the landscape of private industrial innovation in Brazil. The main point is to verify to what extent this tax relief has contributed to the fostering of innovation in the country. To achieve this broad objective, three specific research questions were devised as axes of investigation, and they are addressed in each of the stand-alone papers that comprise this thesis. I begin by assessing whether the incentives have impacted the volume of innovation investment of beneficiary firms. This first analysis also considers the effect of the policy on innovation outputs and firms\' performance. The second research question considers the behavioral additionality, estimating changes caused by the incentives on the composition of the bundle of innovation investments and on the type of innovation pursued by firms. The third investigation assesses whether the reduction of the tax burden has attracted international innovation investment by diverting it from alternative destinations, thus testing the \'footloose R&D\' argument for the Brazilian case. The first two papers use microdata on Brazilian firms from the Industrial Innovation Survey (PINTEC) and other sources, and the impact is estimated through propensity score matching with difference-in-differences. The third study relies on aggregate country data, mainly on activities of foreign affiliates of U.S. multinationals and international patent applications; and panel data estimators are applied to measure and test the correlation of the Brazilian policy with international innovation investment directed to other countries. The main findings of the thesis are: (a) the average impact of the policy on R&D expenditures in 2011 was around five hundred thousand Brazilian reais, or 6.8% of the mean R&D spending of beneficiary firms, which is less than the average benefit per firm in the same year, suggesting some level of crowding-out in the short-run; (b) incentives also positively affected the size of R&D personnel (average effect represents 16% of the average size of R&D staff); (c) the policy raised the chances of firms to innovate between 2009 and 2011 by 16%; (d) incentives positively impacted company\'s growth around 5% of the mean number of employees of incentivized enterprises in 2011; (e) R&D intensity of the bulk of innovative activities increased 9.5% because of the incentives; (f) part of the R&D increase was counterbalanced by a reduction effect on spending with acquisition of external knowledge and introduction of innovations in the market; (g) beneficiary firms hired more researchers with undergraduate degrees only as an effect of the policy (18.5% of the average number of their research personnel with such educational level); and (h) in the case of multinational groups, the increase in innovation investment does not seem to have been caused by the diversion of investment from other countries. The empirical investigations present clear evidence of the three dimensions of policy impact: input, output and behavioral additionality. A number of implications are drawn from the studies for the improvement of the policy design.